Effect of the cranberry ( Vaccinium macrocarpon ) juice on reducing dentin erosion: an in vitro study - Melissa Thiemi KATO; Cristiane de Almeida Baldini CARDOSO; Maisa Camillo JORDÃO; Renato Palhano de Oliveira GALVÃO; Ana Gabriela Silva ISCUISSATI; Angela Mitie Otta KINOSHITA; Marília Afonso Rabelo BUZALAF (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract Vaccinium macrocarpon (cranberry) is a fruit that has an inhibitory effect on matrix metalloproteinases (MMPs) present in dentin and saliva. The inhibition of MMPs has been shown to prevent dentin erosion. The aim of this study was to analyze the effect of cranberry juice on the reduction of dentin erosion in vitro. Specimens of bovine dentin (4×4×2 mm) were randomized and divided into 4 groups (n = 17/group): distilled water (C-control, pH 7.2); green tea extract solution containing 400 µm epigallo-catechin-gallate (EGCg, positive control, pH 4.5); 10% cranberry extract (CrE, pH 3.9), and cranberry juice (CrJ, Cranberry JuxxTM, pH 2.8). Specimens were submitted to erosive pH cycles for 5 days. Each day, four demineralizations were carried out with 0.1% citric acid (90 s). After the acid challenges, specimens were rinsed and kept in treatment solutions for 1 min; afterwards, they were rinsed and stored in artificial saliva for 1 h at 37°C (or overnight at the end of each day). After the experimental period of 5 days, dentin loss was evaluated by contact profilometry. Data were analyzed by ANOVA and Tukey's test (p < 0.05). Dentin loss (µm ± SD) was significantly lower for all treatments (EGCg = 9.93 ± 2.90; CrE = 12.10 ± 5.44; CrJ = 11.04 ± 5.70) compared to control (21.23 ± 11.96), but it did not significantly differ from each other. These results indicate that the commercial cranberry juice, despite its low pH, is able to reduce dentin erosion, which might be due to the ability of cranberry components to inhibit MMPs.